Global emission estimates and radiative impact of C4F10, C5F12, C6F14, C7F16 and C8F18 - R. G. Prinn; J. B. Burkholder; M. Baasandorj; M. Rigby; D. J. Ivy (Atmospheric Chemistry and Physics, 2012)
Global emission estimates based on new atmospheric observations are presented for the acylic high molecular weight perfluorocarbons (PFCs): decafluorobutane (C4F10), dodecafluoropentane (C5F12), tetradecafluorohexane (C6F14), hexadecafluoroheptane (C7F16) and octadecafluorooctane (C8F18). Emissions are estimated using a 3-dimensional chemical transport model and an inverse method that includes a growth constraint on emissions. The observations used in the inversion are based on newly measured archived air samples that cover a 39-yr period, from 1973 to 2011, and include 36 Northern Hemispheric and 46 Southern Hemispheric samples. The derived emission estimates show that global emission rates were largest in the 1980s and 1990s for C4F10 and C5F12, and in the 1990s for C6F14, C7F16 and C8F18. After a subsequent decline, emissions have remained relatively stable, within 20%, for the last 5 yr. Bottom-up emission estimates are available from the Emission Database for Global Atmospheric Research version 4.2 (EDGARv4.2) for C4F10, C5F12, C6F14 and C7F16, and inventories of C4F10, C5F12 and C6F14 are reported to the United Nations' Framework Convention on Climate Change (UNFCCC) by Annex 1 countries that have ratified the Kyoto Protocol. The atmospheric measurement-based emission estimates are 20 times larger than EDGARv4.2 for C4F10 and over three orders of magnitude larger for C5F12 (with 2008 EDGARv4.2 estimates for C5F12 at 9.6 kg yr−1, as compared to 67±53 t yr−1 as derived in this study). The derived emission estimates for C6F14 largely agree with the bottom-up estimates from EDGARv4.2. Moreover, the C7F16 emission estimates are comparable to those of EDGARv4.2 at their peak in the 1990s, albeit significant underestimation for the other time periods. There are no bottom-up emission estimates for C8F18, thus the emission rates reported here are the first for C8F18. The reported inventories for C4F10, C5F12 and C6F14 to UNFCCC are five to ten times lower than those estimated in this study. In addition, we present measured infrared absorption spectra for C7F16 and C8F18, and estimate their radiative efficiencies and global warming potentials (GWPs). We find that C8F18's radiative efficiency is similar to trifluoromethyl sulfur pentafluoride's (SF5F3) at 0.57 W m−2 ppb−1, which is the highest radiative efficiency of any measured atmospheric species. Using the 100-yr time horizon GWPs, the total radiative impact of the high molecular weight perfluorocarbons emissions are also estimated; we find the high molecular weight PFCs peak contribution was in 1997 at 24 000 Gg of carbon dioxide (CO2) equivalents and has decreased by a factor of three to 7300 Gg of CO2 equivalents in 2010. This 2010 cumulative emission rate for the high molecular weight PFCs is comparable to: 0.02% of the total CO2 emissions, 0.81% of the total hydrofluorocarbon emissions, or 1.07% of the total chlorofluorocarbon emissions projected for 2010 (Velders et al., 2009). In terms of the total PFC emission budget, including the lower molecular weight PFCs, the high molecular weight PFCs peak contribution was also in 1997 at 15.4% and was 6% of the total PFC emissions in CO2 equivalents in 2009.